Patients Undergoing Bariatric Surgery: a Special Risk Group for Lifestyle, Emotional and Behavioral Adaptations During the COVID-19 Lockdown. Lessons from the First Wave - Andreu, Alba; Flores, Lilliam; Molero, Judit; Mestre, Carla; Obach, Amadeu; Torres, Ferran; Moizé, Violeta; Vidal, Josep; Navinés, Ricard; Peri, Josep M.; Cañizares, Silvia (Obesity surgery, 2022)
Objectives To determine how the COVID-19 lockdown influenced the lifestyle, eating behavior, use of substances, mental health, and weight in patients who had undergone bariatric surgery (BS) and explore the self-perception of one’s own health and fears related to COVID-19. Methods We performed a cross-sectional exploratory study in obesity patients who had undergone BS surgery > 1 year previously in a university hospital. Assessment was performed 40 days after initiating lockdown and included 2 periods: from April 24 until May 8 and during the initial de-escalation period: from May 9 until 22, 2020. A structured telephone interview and an online survey were administered. Results One hundred eighty-eight patients were interviewed; 156 also responded to the online survey (77% females, mean age 53.46 ± 10.48 years, mean follow-up 5.71 ± 4.30 years). Dietary habits were affected in 72% of the participants, with 15% reporting better diet planning; 83.5% reported having more sedentary behaviors; 27% and 36% showed depression and anxiety, respectively; and 45% of participants reported bad sleep quality. In relation to changes in the use of any substance, the use increased in the majority of patients who were previously users. Self-perception of one’s own health and fears related to COVID-19 were only moderate. Finally, emotional eating and time since BS were statistically significant risk factors for predicting weight gain. Conclusions Lockdown during COVID-19 pandemic negatively influenced the lifestyle, mental health, substance use, and weight in BS patients. These alterations were somewhat similar to those observed in the general population but more severe and with important clinical implications. Graphical abstract